2016
DOI: 10.1016/j.csl.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparing human and automatic speech recognition in a perceptual restoration experiment

Abstract: Speech that has been distorted by introducing spectral or temporal gaps is still perceived as continuous and complete by human listeners, so long as the gaps are filled with additive noise of sufficient intensity. When such perceptual restoration occurs, the speech is also more intelligible compared to the case in which noise has not been added in the gaps. This observation has motivated so-called 'missing data' systems for automatic speech recognition (ASR), but there have been few attempts to determine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Source localisation and source identification could then interact in an ongoing iterative process. In addition, the framework described here could be integrated with an approach that uses source models to 'perceptually restore' parts of the target sound that have been masked [33]. Another future direction is the extension to cross-modal control.…”
Section: Discussionmentioning
confidence: 99%
“…Source localisation and source identification could then interact in an ongoing iterative process. In addition, the framework described here could be integrated with an approach that uses source models to 'perceptually restore' parts of the target sound that have been masked [33]. Another future direction is the extension to cross-modal control.…”
Section: Discussionmentioning
confidence: 99%
“…Mel is pitch unit. Pitch is a subjective psychological quantity, and it is the sense of human auditory system to sound frequency [8]. Through years of research on human ear auditory system, scholars have found that the sensitivity of human ear auditory system to different frequencies of signals is different.…”
Section: Acoustic Featuresmentioning
confidence: 99%